Generation of in vivo-like multicellular liver organoids by mimicking developmental processes: A review - Ayumu Okumura; Kenji Aoshima; Naoki Tanimizu (Regenerative Therapy)
Liver is involved in metabolic reactions, ammonia detoxification, and immunity. Multicellular liver tissue cultures are more desirable for drug screening, disease modeling, and researching transplantation therapy, than hepatocytes monocultures. Hepatocytes monocultures are not stable for long. Further, hepatocyte-like cells induced from pluripotent stem cells and in vivo hepatocytes are functionally dissimilar. Organoid technology circumvents these issues by generating functional ex vivo liver tissue from intrinsic liver progenitor cells and extrinsic stem cells, including pluripotent stem cells. To function as in vivo liver tissue, the liver organoid cells must be arranged precisely in the 3-dimensional space, closely mimicking in vivo liver tissue. Moreover, for long term functioning, liver organoids must be appropriately vascularized and in contact with neighboring epithelial tissues (e.g., bile canaliculi and intrahepatic bile duct, or intrahepatic and extrahepatic bile ducts). Recent discoveries in liver developmental biology allows one to successfully induce liver component cells and generate organoids. Thus, here, in this review, we summarize the current state of knowledge on liver development with a focus on its application in generating different liver organoids. We also cover the future prospects in creating (functionally and structurally) in vivo-like liver organoids using the current knowledge on liver development.